2008
DOI: 10.1017/s0007114507801097
|View full text |Cite
|
Sign up to set email alerts
|

No effect ofn-3 long-chain polyunsaturated fatty acid (EPA and DHA) supplementation on depressed mood and cognitive function: a randomised controlled trial

Abstract: Low dietary intakes of the n-3 long-chain PUFA (LCPUFA) EPA and DHA are thought to be associated with increased risk for a variety of adverse outcomes, including some psychiatric disorders. Evidence from observational and intervention studies for a role of n-3 LCPUFA in depression is mixed, with some support for a benefit of EPA and/or DHA in major depressive illness. The present study was a double-blind randomised controlled trial that evaluated the effects of EPA þ DHA supplementation (1·5 g/d) on mood and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(215 citation statements)
references
References 49 publications
8
202
5
Order By: Relevance
“…Their major theory was that a meal high in carbohydrate increased the rate that tryptophan entered the brain, leading to an increase in the level of the neurotransmitter serotonin that modulates mood. As for fat, it is thought that in many countries current population intakes of the n-3 long-chain PUFA (LCPUFA; also known as long chain omega-3 fatty acids) EPA and DHA are lower than optimal for a variety of health outcomes [2,4]. However, Peter J. Rogers' [5] studies that have shown substantially increasing EPA and DHA intake for 3 months was found not to have beneficial or harmful effects on mood in mild to moderate depression.…”
Section: Introductionmentioning
confidence: 99%
“…Their major theory was that a meal high in carbohydrate increased the rate that tryptophan entered the brain, leading to an increase in the level of the neurotransmitter serotonin that modulates mood. As for fat, it is thought that in many countries current population intakes of the n-3 long-chain PUFA (LCPUFA; also known as long chain omega-3 fatty acids) EPA and DHA are lower than optimal for a variety of health outcomes [2,4]. However, Peter J. Rogers' [5] studies that have shown substantially increasing EPA and DHA intake for 3 months was found not to have beneficial or harmful effects on mood in mild to moderate depression.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, have produced confusing results. While a few studies have reported beneficial effects of n-3 PUFAs supplementation on depression (Nemets et al, 2002;Peet and Horrobin, 2002), other studies have reported no effect (Marangell et al, 2003;Rogers et al, 2008). A recent meta-analysis has concluded that perhaps only EPA, and not DHA, has beneficial effects on depression, which has led to the mixed results reported in clinical studies (Martins, 2009).…”
Section: Depressionmentioning
confidence: 99%
“…Poland). British researchers [56] conducted a large double-blind randomised controlled trial to evaluate the effects of EPA+DHA supplementation (1,5 g/d) on mood and cognitive function in mildly to moderately depressed individuals (190 participants completed 12 weeks intervention). Compliance, confirmed by plasma fatty acid concentrations, was good, but there was no evidence of a difference between supplemented and placebo groups in the depression subscale of DASS (Depression, Anxiety and Stress Scales) at 12 weeks (adjusted difference in mean: -1,0; 95% CI; P=0,27).…”
Section: Nutrients and Affective Functionmentioning
confidence: 99%